2022
DOI: 10.1007/s00394-022-02885-0
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean diet among adults in Mediterranean countries: a systematic literature review

Abstract: Background and aim While the Mediterranean diet (MD) is promoted in non-Mediterranean countries, inhabitants of Mediterranean countries seem to be shifting away from this healthy diet. The aim of this study is to provide an overview of MD adherence in the general adult population of Mediterranean countries. Methods A systematic review was conducted following the PRISMA 2020 (Preferred Reporting Items for Systematic Review and Meta-Analysis) guidelines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
55
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 87 publications
14
55
1
3
Order By: Relevance
“…Moreover, evidence is present that improved health and longevity results from prolonged exposure to this dietary pattern, emphasizing the time factor and the actual moment of its acquisition. However, in several instances, Mediterranean populations have been showing moderate adherence to the Mediterranean diet in the past 10 years [ 18 ], which suggests the need for improving adherence to the Mediterranean diet even in the countries of its origin. In the future, the ways in which a palatable and healthful dietary pattern, such as the Mediterranean diet, can be communicated and promoted need to be investigated beyond medical and nutrition authorities, for example, by employing culinary and marketing strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, evidence is present that improved health and longevity results from prolonged exposure to this dietary pattern, emphasizing the time factor and the actual moment of its acquisition. However, in several instances, Mediterranean populations have been showing moderate adherence to the Mediterranean diet in the past 10 years [ 18 ], which suggests the need for improving adherence to the Mediterranean diet even in the countries of its origin. In the future, the ways in which a palatable and healthful dietary pattern, such as the Mediterranean diet, can be communicated and promoted need to be investigated beyond medical and nutrition authorities, for example, by employing culinary and marketing strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the relevant change in the society features and the associated globalization that occurred in the last half-century and are still ongoing impacted and still impact the relationship between local habits and adherence to the Mediterranean diet, sometimes in opposite directions. A very recent systematic analysis of adherence to the Mediterranean diet among adults in a large set of Mediterranean countries reported that most available studies (in the 2010–2021 period) are from European Mediterranean countries, with fewer studies from Mediterranean countries in North African and Middle Eastern regions [ 18 ]. In general, low or moderate adherence was reported by the different studies, without major sex and age differences.…”
Section: Adherence To the Mediterranean Diet And Geographic Location ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, dietitians conducting the interviews had completed a three-day workshop, and received training on proper data collection, which can reduce interviewing bias. Lastly, a recent systematic review aiming to characterize the adherence to the MeDi in the general adult population of Mediterranean countries observed that most identified studies related to MeDi pertained to European Mediterranean countries with fewer studies from the Middle Eastern and North African Mediterranean countries, showing a clear gap in this research area [ 70 ]. Therefore, the current study helps with the understanding of different MeDi types and allows the comparison of dietary habits between different countries around the Mediterranean basin.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the well-established health benefits of the Mediterranean diet, there is evidence of a gradual deviation from this dietary pattern within Mediterranean populations [ 13 , 14 , 15 ]. For instance, a longitudinal analysis of worldwide dietary data based on Food and Agriculture Organization Food Balance Sheets revealed that the mean Mediterranean Adequacy Index (computed by dividing the sum of the percentage of total energy from typical Mediterranean food groups by the sum of the percentage of total energy from non-typical Mediterranean food groups) decreased from 3.46 ± 1.28 in 1961–1965 to 2.03 ± 0.90 in 2000–2003 and 2.00 ± 0.93 in 2004–2011 within Mediterranean countries [ 13 ].…”
Section: Introductionmentioning
confidence: 99%